Eco-friendly laccase and cellulase enzymes pretreatment for optimized production of high content lignin-cellulose nanofibrils. - DIAS, M. C. (2022)
Lignin-cellulose nanofibrils (LCNF) are of attracting an increasing interest due to the benefits of maintaining the lignin in the nanomaterial composition. The production of LCNF requires considerable energy consumption, which has been suppressed employing pretreatment of biomass, in which it highlights those that employ enzymes that have the advantage of being more environmentally friendly. Some negative aspects of the presence of lignin in the fiber to obtain cellulose nanofibrils is that it can hinder the delamination of the cell wall and act as a physical barrier to the action of cellulase enzymes. This study aimed to evaluate the impact of a combined enzymatic pretreatment of laccase and endoglucanase for high content lignin LCNF production. The morphological and chemical properties, visual aspect and stability, crystallinity, mechanical properties, rheology, barrier properties and quality index were used to characterize the LCNF. The laccase loading used was efficient in modifying the lignin to facilitate the action of the endoglucanase on cellulose without causing the removal of this macromolecule. This pretreatment improved the quality of LCNF (61 ± 3 to 71 ± 2 points) with an energy saving of 42% and, therefore, this pretreatment could be suitable for industrial production for a variety of applications.